Agricultural co-operatives for managing natural capital to achieve UN Sustainable Development Goals 12 to 15: A conceptual framework - Ghauri, Shahid; Jackson, Elizabeth; Marinova, Dora; Mohammadi, Hossein (Elsevier, 2022)
Natural capital is becoming an important topic for global biodiversity and sovereign risk of nations for their food supply chains which can be linked to the United Nations Sustainable Development Goals 12–15. In this paper we explored the literature to develop a conceptual framework to determine how primary industry co-operatives (such as in agriculture and aquaculture) can play a role in managing natural capital. The conceptual framework developed shows that members of co-operatives have roles to act within their organisation that utilise natural capital. Acting out these roles may see the co-operative become pro-active in governing its natural capital based on economic and social goals which are guided by the co-operative principles and values. Working with the financial services sector, co-operatives would be able to engage with their members to educate and share knowledge on strategies to manage and/or mitigate the risk of natural capital depletion. This can be managed through farm management techniques and financial instruments such as credit and insurance.